Analysis of the flow of shipping goods through containers at PT Allfore Logistik - Fontana, Mona (International Publisher, 2022)
Economic development requires sufficient and adequate transportation services. Without transportation as a supporting facility, satisfactory results cannot be expected to be achieved in developing a country. The purpose of this research is to find out the process of sending goods through containers. This research method uses qualitative research by collecting data through interviews, observation and literature study. The results of this study are that the process of sending goods through containers via train at PT Berkat Mandiri Logistik North Jakarta has several stages, namely making Delivery Orders, Making internal shipping and external shipping, Preparing empty containers, Transferring containers to cars, Making travel documents, Stuffing processes, Delivery to trains, Delivery to Surabaya, Dooring process.